sweetwater's SIMPLE HOME : SEW SOMETHING HANDMADE FOR EVERY ROOM . 35 PROJECTS - Burnett, Lisa (Lisa Eisenach); Kendrick, Susan, (Susan Eisenach); Eisenach, Karla, (Karla Gordon) (Lafayette, California : Stash Books, 2011)
Add those little personal touches that make a house a home with these 36 inspiring and beginner-friendly projects from the mother and daughters team at Sweetwater Designs.
Keywords: House furnishings; Machine sewing